2011
DOI: 10.22547/ber/3.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Problems Facing The Hayatabad Industrial Estate And Their Implications On Policy Formulation

Abstract: The provinces of Khyber Pakhtunkhwa Province (KPK) and Baluchistan have historically lagged behind other provinces in the race for industrialization because of their geographical disadvantage and the law and order situation prevailing in their regions. Recent figures show that the number of closures and ailing industrial units in KPK has been increasing. Statistics indicate that 55% of firms administered by SIDB 1 and 64% of firms administered by SDA 2 have closed down. In the wake of increase in terrorism act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The main theme of this project is to supply electricity to the connected areas to boost business activities. KPK is the province where more than 60% of operated businesses were closed down [44]. Hence, supplying adequate electricity is need of the day for current and potential business.…”
Section: Suki Kinari Hydro Power Station Kpkmentioning
confidence: 99%
See 1 more Smart Citation
“…The main theme of this project is to supply electricity to the connected areas to boost business activities. KPK is the province where more than 60% of operated businesses were closed down [44]. Hence, supplying adequate electricity is need of the day for current and potential business.…”
Section: Suki Kinari Hydro Power Station Kpkmentioning
confidence: 99%
“…These projects are intended to achieve long term benefits such as creating employment opportunities, environmental safety and educational improvement [83]. Lack of infrastructure and facilities, particularly electricity load shedding is the major barrier of business growth in rural areas [44]. Hence, CPEC is expected to play a very positive role in developing the rural areas that would overcome these issues, by generating new opportunities for the people in these areas.…”
Section: Plos Onementioning
confidence: 99%
“…For instance, Gul and Nouman (2009) suggested that there is a great need for private and government organizations to support SMEs regarding innovation in order to enhance the sustainability of the industrial sector. Because healthy industrial sector cannot be underestimated in productivity and a higher standard of living in emerging markets such as Pakistan (Shah et al, 2011).…”
Section: Implications For Practicementioning
confidence: 99%
“…Majority of businesses are SMEs which contribute more than 30% to GDP of Pakistan (Akhtar, Ismail, Hussain, & Umair-ur-Rehman, 2015). However, there are numerous problems faced by SMEs in the country that decline their survival and performance (Shah, Gul, & Aziz, 2011). On the Index of Ease of Doing Business (IEDB) perspective, Pakistan has ranked at 144 th number out of 190 countries (World Bank, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is inevitable for businesses to gain the requisite resources for the smooth operation of the allied activities necessary for running the businesses, particularly in this hyper-turbulent business environment. For instance, in emerging economies such as Pakistan, around half of the SMEs fail in the initial stages of the business cycle, just because of lack of resources, capabilities and support (Shah, Gul & Aziz, 2011). In China, 67% of ventures fail in their infancy while an overall 85% of ventures fail within the first 10 years of their operations (Parnell, Long & Lester, 2015).…”
Section: Introductionmentioning
confidence: 99%